Analisis Kebutuhan Perubahan Untuk Meningkatkan Kepuasan Pelanggan: Study Kasus : Vibes Barbershop & Coffee - Syahfitri; Nuri Aslami (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
People's needs and lifestyles are increasing following the times, advances in technology and information, as well as increasing living standards. Barbershops have advantages and the impression of being a trendy barbershop. This shows a change in people's behavior that requires direction to find out which models are trending regarding hairstyles. This study uses qualitative research methods with data collection techniques through direct observation and interviews with customers of Vibes Barbershop And Coffee as well as providing comments via Google Maps. No negative feedback has been given by customers via Google Maps, and customers are satisfied with the changes that have been made.